Answer:
Option B. m(n) = –5.75 –¼n
Step-by-step explanation:
The sequence is given below:
–6, –25/4, –13/2, –27/4, –7
Next, we shall determine the common difference.
Common difference (d) = 2nd – First
2nd term = –25/4
First term = –6
d = –25/4 – – 6
d = –25/4 + 6
d = –6.25 + 6
d = –0.25 = –¼
Finally, we shall determine the nth term
Tₙ = a + (n –1)d
First term (a) = –6
Common difference (d) = –¼
Tₙ = a + (n –1)d
Tₙ = –6 + (n –1)–¼
Tₙ = –6 –¼n + ¼
Tₙ = –6 + ¼ –¼n
Tₙ = –6 + 0.25 –¼n
Tₙ = –5.75 –¼n
Thus, the nth term is given by:
m(n) = –5.75 –¼n